Description of Musculoskeletal Disorders in Dental Professional Program Students at Dental and Oral Hospital of Universitas Muhammadiyah Semarang - Farah Fathia Fauzia; Ulfa Nurullita; Dwi Windu Kinanti Arti (Dental and Oral Hospital of Universitas Muhammadiyah Semarang, 2023)
Background: Dentists when performing treatment to patients require accuracy which results in the dentist having to look down at the patient (awkward position) which can cause Musculoskeletal Disorders (MSDs). This complaint can also occur in dental students because if they perform treatment in the wrong position, repeatedly, for a long time it can cause Musculoskeletal Disorders (MSDs). The aim of this study was to know the description of Musculoskeletal Disorders complaints in Dentist Professional Program Students at RSGM Unimus. Method: This research is a descriptive study with a cross-sectional approach. The subjects were dental students with more than one year of practice at RSGM Unimus as many as 38 people with sampling technique using accidental sampling. The data collection technique was done by interview using Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) instrument. Result: Most respondents were female (84.2%), 25 years old (39.5%), and the length of daily practice was about 2 hours (39.5%). Most respondents had mild Musculoskeletal Disorders (MSDs) complaints in all parts of the body, but there were also severe complaints in the lower back (23.7%), neck (7.9%), upper back (7.9%), and waist or buttocks (7.9%). Conclusion: Musculoskeletal Disorders (MSDs) complaints among dental students at RSGM Unimus are still in the low category but there are also body parts that have severe categories, namely the lower back, neck, upper back, and waist or buttocks.